Antinociceptive Effect of Memantine and Morphine on Vincristine-induced Peripheral Neuropathy in Rats - Park, Byoung Yoon (The Korean Pain Society, 2010)
BACKGROUND: Vincristine-induced peripheral neuropathy is a major dose limiting side effect and thus effective therapeutic strategy is required. In this study, we investigated the antinociceptive effect of memantine and morphine on a vincristine-induced peripheral neuropathy model in rats. METHODS: Male Sprague-Dawley rats weighing 220-240 g were used in all experiments. Rats subsequently received daily intraperitoneal injections of either vincristine sulfate (0.1 ml/kg/day) or saline (0.1 ml/kg/day) over 12 days, immediately following behavioral testing. For assessment of mechanical allodynia, mechanical stimuli using von Frey filament was applied to the paw to measure withdrawal threshold. The effects of N-methyl-D-aspartate receptors antagonist (memantine; 2.5, 5, 10 mg/kg intraperitoneal), opioid agonist (morphine; 2.5, 5, 10 mg/kg intraperitoneal) and vehicle (saline) on vicristine-induced neuropathy were evaluated. RESULTS: Mechanical allodynia developed over the course of ten daily injections of vincristine relative to groups receiving saline at the same time. Morphine abolished the reduction in paw withdrawal threshold compared to vehicle and produced dose-responsiveness. Only the highest dose of memantine (10 mg/kg) was able to increase paw withdrawal threshold compared to vehicle. CONCLUSIONS: Systemic morphine and memantine have an antinociceptive effect on the vincristine-induced peripheral neuropathy model in rats. These results suggest morphine and memantine may be an alternative approach for the treatment of vincristine-induced peripheral neuropathic pain.